2021
DOI: 10.3390/microorganisms9091864
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal Microbiota of the Sexually Transmitted Infections Caused by Chlamydia trachomatis and Trichomonas vaginalis in Women with Vaginitis in Taiwan

Abstract: The three most common sexually transmitted infections (STIs) are Chlamydia trachomatis (CT), Neisseria gonorrhoeae (GC) and Trichomonas vaginalis (TV). The prevalence of these STIs in Taiwan remains largely unknown and the risk of STI acquisition affected by the vaginal microbiota is also elusive. In this study, a total of 327 vaginal swabs collected from women with vaginitis were analyzed to determine the presence of STIs and the associated microorganisms by using the BD Max CT/GC/TV molecular assay, microbia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 58 publications
3
25
0
1
Order By: Relevance
“…Without timely intervention and treatment, it may further develop precancerous lesions, cause infertility and other symptoms, and pose a serious threat to women's life and health [ 1 , 2 ]. Incomplete statistics show that the incidence of sexual vagina trichomonad disease is on the rise year by year, and such diseases with high infectivity, clinical symptoms of vaginal ectopic, itching, leucorrhoea increase, etc., and if treatment is not in place, there will be a relapse, greatly increased the psychological pressure and reduce the quality of life in patients [ 3 ]. Therefore, it is of great significance to find a safe and effective treatment to improve the prognosis and quality of life of patients with trichomoniasis vaginitis [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Without timely intervention and treatment, it may further develop precancerous lesions, cause infertility and other symptoms, and pose a serious threat to women's life and health [ 1 , 2 ]. Incomplete statistics show that the incidence of sexual vagina trichomonad disease is on the rise year by year, and such diseases with high infectivity, clinical symptoms of vaginal ectopic, itching, leucorrhoea increase, etc., and if treatment is not in place, there will be a relapse, greatly increased the psychological pressure and reduce the quality of life in patients [ 3 ]. Therefore, it is of great significance to find a safe and effective treatment to improve the prognosis and quality of life of patients with trichomoniasis vaginitis [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics of the studies included in the Systematic Review are summarized in Table 1 . The papers were published between 2017 and 2021 and were conducted on almost all continents, with 8 of them performed in Europe [ 14 , 19 , 21 , 23 , 24 , 25 , 26 , 29 ], 2 in North America [ 17 , 20 ], 3 in Asia [ 16 , 22 , 27 ], 2 in Africa [ 18 , 28 ] and 1 in Australia [ 15 ]. 13 case-control [ 14 , 16 , 17 , 18 , 19 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ], 2 cohort [ 15 , 20 ] and 1 cross-sectional [ 21 ] studies were included, and all of them involved reproductive-age women, who tested positive for C. trachomatis infection via nucleic acid amplification tests (NAATs), alongside matched uninfected women as control group.…”
Section: Resultsmentioning
confidence: 99%
“…Since the first attempts, an increasing body of research, investigating the composition of cervicovaginal microbiota associated with C. trachomatis genital infection via 16s rRNA gene sequencing, has been published [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. The main findings evidenced the association of a microbiota dominated by L. iners (CST-III) or by different anaerobic bacteria (CST-IV) with C. trachomatis infection, although the specific bacterial species identified varied significantly amongst the different studies and, hence, it is very challenging to compare and summarize results, often leading to controversy.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, recently, many authors have focused on the correlation between CT infection and the vaginal environment [ 6 , 7 , 8 , 9 , 10 , 11 ]. Some cross-sectional studies have demonstrated that the presence of bacterial vaginosis (BV), a dysbiosis status with a depletion of lactobacilli and the predominance of other anaerobic species, increases the risk of STI acquisition, including genital CT infections [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…A network of different anaerobes, such as Gardnerella vaginalis , Prevotella amnii , Prevotella buccalis , Prevotella timonensis , Aerococcus christensenii , and Variovorax guangxiensis , has been identified as a potential biomarker of CT genital infection [ 11 ]. Moreover, in CT-positive patients, the vaginal microbiota is often dominated by Lactobacillus iners , a transitional species characterized by low antimicrobial activity [ 9 ].…”
Section: Introductionmentioning
confidence: 99%